The role of general dynamic coordination in the handwriting skills of children - Scordella, Andrea; Di Sano, Sergio; Aureli, Tiziana; Cerratti, Paola; Verratti, Vittore; Fanò-Illic, Giorgio; Pietrangelo, Tiziana (Frontiers in Psychology, 2015)
Difficulties in handwriting are often reported in children with developmental coordination disorder (DCD), and they represent an important element in the diagnosis. The present study was aimed at investigating the relation between motor coordination and handwriting skills, and to identify differences in handwriting between children without and with coordination difficulties. In particular, we asked whether visual-spatial skills have a role as mediating variables between motor coordination and handwriting. We assessed motor coordination as well as graphic abilities in children aged 7-10 years. Moreover, we evaluated their visual-motor integration, visual-spatial skills, and other cognitive abilities (memory and planning). We found no relation between motor coordination and handwriting skills, while visual-spatial skills (measured by a visual-constructive task) were related with both. Our conclusion is that visual-spatial skills are involved both in general motor coordination and in handwriting, but the relationship involves different aspects in the two cases.